2018
DOI: 10.1007/s40097-018-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanocomposite with Tarragon leaf extract and assessment of antibacterial activity

Abstract: The aqueous extract of Tarragon, as a reducing agent, was used to synthesize silver-montmorillonite (MMT) nanocomposite (Ag-MMT-NPs) in the batch method. The leaf extract and metal solution concentrations were optimized to improve Ag-MMT-NPs synthesis in 48 h. For characterizing the nanocomposite, powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Transmission electron microscopy (TEM), and UV-Vis spectroscopy were performed. The peak was observed at 437 nm on the UV-Vis spectrum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Synthesis of nanoparticles using microbes have great potential and huge benefits to human, because they eliminate the use of toxic chemicals and minimize the production cost involved in the synthesis. One of the main advantages of biosynthesis of metal nanoparticles is their immense role in the protection of environment which is also the ultimate target of other green technologies [36,37]. Recently, mycogenesis of nanoparticles has attracted much attention of researchers; however, the exact mechanism related to the synthesis has not been understood yet.…”
Section: Mycogenesis Of Metal Nanoparticles and Their Possible Mechanismmentioning
confidence: 99%
“…Synthesis of nanoparticles using microbes have great potential and huge benefits to human, because they eliminate the use of toxic chemicals and minimize the production cost involved in the synthesis. One of the main advantages of biosynthesis of metal nanoparticles is their immense role in the protection of environment which is also the ultimate target of other green technologies [36,37]. Recently, mycogenesis of nanoparticles has attracted much attention of researchers; however, the exact mechanism related to the synthesis has not been understood yet.…”
Section: Mycogenesis Of Metal Nanoparticles and Their Possible Mechanismmentioning
confidence: 99%
“…Green synthesis methods are simple, easy and pleasant, that's why a lot of scientists use the usual reduction reactions initiated with the use of natural chemical compounds [24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of bands at that spectral range suggested that the capping capping agent of biosynthesized nanoparticles possesses an aromatic amines group with specific signatures of amide linkages between amino acid residues in the proteins along with infrared region of the electromagnetic spectrum. The proteins are potential biomolecules responsible for the reduction and capping of the AgNPs synthesized [26,27].…”
Section: Resultsmentioning
confidence: 99%